Acceleration of skin wound healing by low-dose indirect ionizing radiation in male rats - Nasrollah Jabbari; Gholam Hossein Farjah; Behnam Ghadimi; Hajar Zanjani; Behnam Heshmatian (Kaohsiung Journal of Medical Sciences, 2017)
A recent hypothesis has revealed that low-dose irradiation (LDI) with ionizing radiation might have a promoting effect on fracture healing. The aim of this study was to investigate the influence of direct (electron beam) and indirect (gamma-ray) low-dose ionizing irradiations on the wound healing process in male rats. In 72 male rats, a full-thickness wound was incised. The animals were randomly assigned to three groups, each with 24 rats. The first two groups were named IG–I and IG–II and respectively exposed to electron and gamma-radiations (75 cGy) immediately after the surgical procedure. The third group was considered as the control (CG) and remained untreated. Skin biopsies from the subgroups were collected on days 3, 7, 15, and 21 after the operation and evaluated using histological and biomechanical methods. Data were analyzed by one-way ANOVA, followed by Tukey's post hoc test using SPSS 20 software. Histological studies of tissues showed that the mean number of fibroblasts, macrophages, blood vessel sections, and neutrophils on the third and seventh days after the surgery in the gamma-treated group was higher than that in both other groups. In contrast, on day 21, the mean number of mentioned cells in the gamma-treated group was lower than in the other two groups. In addition, the mean maximum stress value was significantly greater in the gamma-treated group. Results of this study showed that gamma-ray irradiation is effective in the acceleration of wound healing.